Sequestration of selenium on calcite surfaces revealed by nanoscale imaging - Putnis, Christine; Renard, F.; King, H.; Montes-Hernandez, G.; Ruiz-Agudo, E. (2013)
Calcite, a widespread natural mineral at the Earth’s surface, is well-known for its capacity to sequester various elements within its structure. Among these elements, selenium is important because of its high toxicity in natural systems and for human health. In the form of selenite (Se(IV)), selenium can be incorporated into calcite during growth. Our in situ atomic force microscopy observations of calcite surfaces during contact with selenium-bearing solutions demonstrate that another process of selenium trapping can occur under conditions in which calcite dissolves. Upon the injection of solutions containing selenium in two states of oxidation (either Se(IV) or Se(VI)), precipitates were observed forming while calcite was still dissolving. In the presence of selenate (Se(VI)), the precipitates formed remained small during the observation period. When injecting selenite (Se(IV)), the precipitates grew significantly and were identified as CaSeO3·H2O, based on SEM observations, Raman spectroscopy, and thermodynamic calculations. An interpretation is proposed where the dissolution of calcite increases the calcium concentration in a thin boundary layer in contact with the surface, allowing the precipitation of a selenium phase. This process of dissolution–precipitation provides a new mechanism for selenium sequestration and extends the range of thermodynamic conditions under which such a process is efficient.